The Impact of Medical Coding on Healthcare Transformation and Bridging the Gap in Pakistan - Sidra Abid; Maha Zehra; Sharmeen Fatima; Hamna Rafiq (ziauddin University, 2024)
In the field of health care, medical coding entails translating diagnoses, treatments, and medical procedures into standardized alphanumeric numbers.  This process is critical in establishing reliable and precise health records among various healthcare providers. Pakistan's healthcare system encounters accessibility and efficiency issues, resulting in billing errors, delayed reimbursement, as well as substantial compromises inpatient treatment. The implementation of ICD-9 and ICD-10 coding systems aids in the classification and retrieval of medical information, which is critical for health managers' decision-making. The adoption of ICD-11 in Pakistan's healthcare system is an important opportunity to improve diagnostic and data precision1. The use of medical coding documentation is critical for accounting precision, avoiding errors, and optimizing reimbursement processes, improving the financial viability of healthcare facilities in resource-constrained situations. Medical coding accuracy is critical because coding errors can lead to erroneous information and have an impact on planning, research, and regulation2.